PERBEDAAN KEBIASAAN BELAJAR DASAR-DASAR GAMBAR TEKNIK ANTARA SISWA PROGRAM KEAHLIAN TEKNIK GAMBAR BANGUNAN SMKN 1 SUMATERA BARAT YANG TINGGAL DI ASRAMA DENGAN YANG TIDAK TINGGAL DI ASRAMA - 502-510 , Farino Pyanto (Universitas Negeri Padang, 2015)
Abstract The aim of this research is to reveal the differences of study habits in learning Basic Engineering Drawing course between students of SMKN 1 West Sumatra who live in dormitory and who do not. This research is done by using experimental approach. The sample of this research are students of Building Drawing Engineering Program of SMKN 1 West Sumatra who live in dormitory and who do not, in academic year 2013/2014. Data are gained by using modified Likert Scale questionnaire and are analyzed by using independent sample T-test. The result of the research shows that the study habits of students who live in dormitory is in good category, while the study habits of students who do not live in dormitory is in poor category. The conclusion of this research is that there are significant differences of study habits in learning Basic Engineering Drawing course between students of SMKN 1 West Sumatra who live in dormitory and who do not. Keywords : Habits, Basic Engineering Drawing course, Dormitory